Study on Relationship of the Resistivity with Specific Heat - Alfredo Olmos Hernández; Reyna Romyna Olmos Hernández (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
We study the relationship between resistivity and specific heat. It is known that the resistivity of a conductor increases when its temperature increases. And the specific heat of a material is found as a function of temperature, so we calculated the resistivity from the specific heat and the temperature variation. The resistivity of a conductor is determined as a function of specific heat, the resistance of a conductor is determined as a function of mass, temperature and specific heat; and the electric field is determined as a function of the specific heat.